(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper, node recovery techniques in Wireless Sensor Networks have studied and an improved node recovery algorithm has developed. LEDIR algorithm has studied and then a new I-LEDIR (improved LEDIR) algorithm has developed and also has compared with previous LEDIR and RIM. The new algorithm is compared to existing algorithms based on three parameters: distance moved, no. of nodes moved and total no. of messages exchanged and the results are presented.